Mental health intervention and treatment of first responders and emergency workers - Beidel, Deborah C.; Bowers, Clint A.; Marks, Madeline R., 1990- (Advances in psychology, mental health, and behavioral studies., 2020)
The stress that comes with being a first responder has been known to lead to depression, anxiety, substance abuse, and suicide. However, few clinicians are informed about these health concerns and how to adequately treat them in this population. Therefore, there is an urgent need for practitioners to understand the latest information regarding treatments that will be useful to this specific population. Mental Health Intervention and Treatment of First Responders and Emergency Workers is an essential reference source that focuses on the latest research for diagnosing and treating mental health.